61 Aed accessibility and bystander defibrillation in out-of-hospital cardiac arrest. (16th April 2018) - Karlsson, L; Sun, CLF; Torp-Pedersen, C; Lippert, FK; Chan, TCY; Folke, F
Abstract : Aim: Inaccessibility of publicly available automated external defibrillators (AEDs) is an issue recently emphasised; 1, 2 however, knowledge of the impact of inaccessibility on bystander defibrillation remains sparse. Method: We identified all public out-of-hospital cardiac arrests (OHCAs) registered by the Copenhagen Mobile Emergency Care Unit physicians (2008–2016), and all publicly available AEDs in Copenhagen (2007–2016) from the Danish AED Network. All recorded OHCAs and AEDs were geocoded, and the true route distances between OHCAs and AEDs were calculated. A covered OHCA was defined as an OHCA with an AED located ≤200 m and AED accessibility was assessed for every AED at the exact time of OHCA. Results: In total, 1, 830 AEDs were registered in Copenhagen. Out of 643 public OHCAs, 261 (40.6%) were covered by a registered AED ≤200 m (median distance: 107.6 m (interquartile range [IQR]: 58.6–146.7)). Of the covered OHCAs, 156 (59.8%) occurred ≤200 m of an accessible AED, and in 105 OHCAs (40.2%) the AED was inaccessible. Compared with OHCAs near an inaccessible AED, OHCAs near an accessible AED were more likely to receive bystander defibrillation (25.0% vs 13.3%, p=0.02) and achieve 30 day survival (49.7% vs 38.0%, p=0.08). Conclusion: The chances of receiving bystander defibrillation nearly doubled if the OHCA was covered by an accessible AED ≤200 m, and the proportion of cases that achieved 30 day survival tended to be higher compared to OHCA cases covered by an inaccessible AED. References: . Sun CL, Demirtas D, Brooks SC, Morrison LJ, Chan TC. Overcoming spatial and temporal barriers to public access defibrillators via optimisation. J Am Coll Cardiol2016;68(8):836–45. . Hansen CM, Wissenberg M, Weeke P, Ruwald MH, Lamberts M, Lippert FK, Gislason GH, Nielsen SL, Kober L, Torp-Pedersen C, Folke F. Automated external defibrillators inaccessible to more than half of nearby cardiac arrests in public locations during evening, nighttime, and weekends. Circulation2013;128(20):2224–31. Conflict of interest: None Funding: Dr. L. Karlsson is supported by a fund from The Danish foundation TrygFonden, who has no influence on study design; in the collection, analysis, or interpretation of data.